Workloads of different soccer-specific drills in professional players - Chena, M.; Morcillo-Losa, J. A.; Rodríguez-Hernández, M. L.; Asín-Izquierdo, I.; Pastora-Linares, B.; Zapardiel, J. C. (Journal of Human Kinetics, 2022)
Soccer is a predominantly tactical sport and, therefore, tactical training has become the most widely used strategy to improve players' performance. The objective of the present study was to assess the workload of soccer-specific drills in professional players over a two-season period in an established context. GPS technology was used to record the data. One hundred and thirty-two (n = 132) soccer-specific drills were studied and grouped by categories. The individual demands of each task were related to the individual competitive profile of each player. The level of physical demand was significantly different in relation to the specific soccer drills analysed. Total distance covered, high-speed running, and the total number of high accelerations and decelerations were significantly higher in competition than in drills used for training sessions (p < .001). The Large-Sided Games (LSG), Big-Position Games (BPG) and Position Games (PG) showed higher maximum running speed values than the rest of the exercises (p < .01). The sum of high accelerations and decelerations values was greater in the Small-Sided Games (SSG) than in BPG (p < .001), Small-Position Games (SPG) (p < .001) and Physical-Technical Circuits (PTC) (p < .001). Significant differences were observed in the exercises analysed according to the player`s position. The current findings provide a detailed description of conditional demands placed on soccer players in different soccer-specific drills during training sessions, in a professional soccer context and according to their playing position, which may be helpful in the development of individualized training programs in other contexts.